2020
DOI: 10.1183/23120541.00220-2019
|View full text |Cite
|
Sign up to set email alerts
|

Mobile health application to support CPAP therapy in obstructive sleep apnoea: design, feasibility and perspectives

Abstract: BackgroundCurrent continuous positive airway pressure (CPAP) devices can be monitored remotely; however, in-person visits are kept for clinical follow-up in order to promote CPAP use and resolve potential side-effects. Mobile health is a promising way to provide remote and easy clinical control for CPAP follow-up and support. We aimed to evaluate the feasibility and acceptance by obstructive sleep apnoea (OSA) patients and healthcare professionals of a newly designed mobile app (Appnea-Q) to promote clinical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…These additional sensors may include ankle accelerometers to estimate leg movements during sleep [8], voltage sensors to measure the electrocardiogram, optic sensors to measure haemoglobin oxygen saturation, and the smartphone microphone to measure respiratory sounds such as snoring. The low-cost and open-source characteristics of our system may also allow integration with third-party mobile health applications such as the recently designed Appnea-Q mobile app [13] as well as with third-party wearable monitors [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These additional sensors may include ankle accelerometers to estimate leg movements during sleep [8], voltage sensors to measure the electrocardiogram, optic sensors to measure haemoglobin oxygen saturation, and the smartphone microphone to measure respiratory sounds such as snoring. The low-cost and open-source characteristics of our system may also allow integration with third-party mobile health applications such as the recently designed Appnea-Q mobile app [13] as well as with third-party wearable monitors [18].…”
Section: Discussionmentioning
confidence: 99%
“…Some CPAP device manufacturers provide web platforms allowing physicians and patients to receive data on compliance, apnea-hypopnea index (AHI) and mask leaks (Table 1). However, companies employ their own proprietary algorithms making it difficult to carefully interpret the results [13]. The lack of standardization also hinders interoperability with existing electronic patient records and may be a problem for health care systems that employ CPAP devices of multiple brands [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17,28] outcomes such as satisfaction and cost-effectiveness. [29,30] Technologies for longitudinal monitoring of lifestyle components and AF risk factors are available and may support a more complete remote assessment and management of AF patients in the future, once these tools can be implemented in existing clinical pathways or emerging mHealth approaches. In addition to the assessment of risk factors, mHealth infrastructures and apps can also be helpful in applying dedicated in-app coaching to improve lifestyle and control risk factors by behavioral changes.…”
Section: Remote Assessment and Management Of Af Risk Factorsmentioning
confidence: 99%
“…[ 17,28 ] Several clinical trials have demonstrated the feasibility of mHealth‐based sleep apnea management compared with a more traditional in‐person care model, suggesting non‐inferiority in terms of adherence to continuous positive airway pressure treatment and compliance as well as functional outcomes such as satisfaction and cost‐effectiveness. [ 29,30 ]…”
Section: Remote Assessment and Management Of Af Risk Factorsmentioning
confidence: 99%